Método didáctico "CLAFEL IV" y su influencia en el Aprendizaje del idioma Inglés en educandos del Tercer Grado de Educación Secundaria - Gastelo Bardales, Julio Cesar (2003)
The present Thesis, is the result of the experimentation about a new didactic method denominated Clafel IV which makes possible the learning of English language. With the applied type and quasi-experimental level the Thesis in mention was applied to students of the third degree of secondary education of Juan Miguel Pérez: Rengifo High School of the county of San Martín, district of Tarapoto. The formulation of the investigative problem has been structured in the relationship that exists among the experimental variables of the didactic method Clafel IV. The nature of the method is in essence, the one of being an instrument to teach to learn English language from the secondary education. The theoretical bases are based in the most relevant pedagogic principles, in which this method is emerged, are: principle of activity, principle of cooperation, principle of sociability or collective, principle of creativity, practical-theoretical principle and the principle of freedom. The theoretical body of the didactic method Clafel IV have been systematized in function to its purpose, its action field, its theoretical support, its structure composed by stages and these by processes. The sample was conformed by twenty-three (23) elected students aleatorily, and who twelve ( 12) students belongs to the experimental group and eleven ( 11 ) students to the control group. The gathering of data was made by means of pre and post tests. The hypothesis was contrasted with the statistical parameter T-student. The hypothesis test was made and then proven the hypotheses by means of the mentioned statistical technique have been ended up concluding that the influence of the didactic method Clafel IV in the learning of English language have beensignif1cant, what this implies the students has been motivated positively for the learning of the language in mention, developing in this way learnigs in the cognitive. procedural and actitudinal part of English language.